PERTANGGUNGJAWABAN PIDANA BAGI PELAKU TINDAK PIDANA PROSTITUSI ONLINE DI TINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (Studi Putusan Nomor 267/Pid.B/2015/PN. Pgp). - Khairul Imam; Syafruddin Kalo; Alvi Syahrin; Marlina Marlina (Universitas Sumatera Utara, 2018)
ABSTRACT Prostitution by using electronic means or the internet is currently developing. Prostitution is a problem that not only involves prostitutes, but more than that it is an activity that involves many people such as pimps, brokers, and consumers who most of the perpetrators are men who often escape the attention of law enforcement officers. Judicial problemat can be seen where punishment can only be done to pimps or pimps while prostitute and client can not be penalized, besides law enforcement in case of online prostitution is very difficult because in transactions prostitution online there are up to cross borders cross country (bordeless). The lack of strict rules on the criminalization of online prostitutes has resulted in the difficulty of this online criminal prostitution to be prevented. The issues raised in this study, namely how the regulation of criminal law against perpetrators of online prostitution crime and pimp responsibility in Decision Number 267/Pid.B/2015/PN. Pgp in review of Law Number 11 Year 2008 About Information And Electronic Transactions To find the answer of this problem, this research use normative law research type which is analytical descriptive, where this normative law research use secondary data as main data with munggunakan data collecting technique done by library study (library reseacrh), and data analysis using method analysis of qualitative data. Analysis of this data is intended based on the picture, the facts obtained will be analyzed carefully to answer the problem. Keywords: Criminal Accountability, Crime, Prostitution, Online.